Skin immunity in wound healing and cancer - Jakovija, Arnolda; Chtanova, Tatyana (Frontiers in Immunology, 2023)
The skin is body’s largest organ. It serves as a barrier to pathogen entry and the first site of immune defense. In the event of a skin injury, a cascade of events including inflammation, new tissue formation and tissue remodeling contributes to wound repair. Skin-resident and recruited immune cells work together with non-immune cells to clear invading pathogens and debris, and guide the regeneration of damaged host tissues. Disruption to the wound repair process can lead to chronic inflammation and non-healing wounds. This, in turn, can promote skin tumorigenesis. Tumors appropriate the wound healing response as a way of enhancing their survival and growth. Here we review the role of resident and skin-infiltrating immune cells in wound repair and discuss their functions in regulating both inflammation and development of skin cancers.